Mapping the Journey of Internet of Things (IoT) Research: A Bibliometric Analysis of Technology Advancements and Research Focus - Adi Nugroho Susanto Putro; Agung Nugroho (West Science Interdisciplinary Studies, 2023)
The Internet of Things (IoT) has ushered in a new era of connectivity, transforming industries and societies across the globe. This research delves into the IoT research landscape through a comprehensive bibliometric analysis, unveiling technological trends and research focuses. The methodology encompasses data collection, preprocessing, advanced bibliometric techniques, and visualization tools. Results highlight key contributors, collaborative networks, research themes, and influential works. Through analysis and visualization, we gain insights into the trajectory of IoT research, its multidisciplinary nature, and the evolving challenges it addresses. This study serves as a compass for researchers, policymakers, and practitioners navigating the intricate IoT ecosystem.